Crisis communication and language strategy: a corpus-based study of governmental covid-19 briefings in Indonesia - Aulia Cika Kartika (CV Narasi Khatulistiwa Indonesia, 2026)
Background: The COVID-19 pandemic required governments worldwide to deliver timely, clear, and persuasive crisis communication to maintain public trust and compliance. Objective: This study aims to examine the lexical patterns, narrative structures, and pragmatic strategies in Indonesian government COVID-19 briefings, focusing on how language was used to manage public understanding and behavior. Method: Using a qualitative corpus-based discourse analysis integrating corpus linguistics, discourse analysis, and speech act/politeness theory, the research analyzed transcripts, press releases, and official video subtitles from March 2020 to December 2021. Results: Findings show that the government consistently employed anchor phrases such as protokol kesehatan alongside phase-specific terminology to balance continuity and adaptability. Narrative structures followed a stable Opening–Problem–Policy–Closing format, reinforced by culturally resonant frames like gotong royong and otoritas ilmiah. Pragmatically, directives dominated but were frequently mitigated through positive politeness strategies to preserve solidarity and trust. These results suggest that Indonesia’s crisis communication effectively integrated informational clarity with cultural sensitivity. Implication: The findings have implications for designing culturally adaptive, trust-oriented governmental communication strategies in future public health emergencies. Novelty: This study shows how corpus-driven discourse patterns and culturally embedded pragmatic strategies work together to sustain clarity, trust, and compliance in governmental crisis communication.